How does technological progress promote carbon productivity? Evidence from Chinese manufacturing industries - Fan, Li-Wei; You, Jianmin; zhang, Wei; Zhou, Peng (Journal of environmental management, 2021)
Technological progress greatly contributes to the promotion of carbon productivity (CP). This study aims to identify an appropriate mode of technological progress that increases CP. A data envelopment analysis-based method was used to investigate the impacts of four forms of technological progress under two classifications of CP: the progress of neutral technology (NT) and capital-embodied technology (CET) under a technological source and the progress of energy technology (ET) and carbon technology (CT) under an abatement process. We applied dynamic panel data models to deeply analyze the different impacts of the four forms of technological progress on the CPs of Chinese manufacturing industries from 1995 to 2015. Results show that (1) a change in ET contributes more to the promotion of CP than a change in CT; (2) a change in CET promotes CP more than a change in NT; and (3) the indirect effect of a change in CET on CP through a change in ET and the indirect effect of a change in NT on CP through a change in CT are advantageous. These findings provide important policy implications in promoting technological progress and improving Chinese MIs’ CPs. Significant policy measures based on theoretical and empirical conclusions are proposed. •Technological progresses promote China's MIs' carbon productivity (CP).•Energy technological change has a positive greater role on CP.•Capital bodied technological change has a positive greater role on CP.•Indirect effect of capital embodied technological change on CP is advantageous.•Indirect effect of neutral technological change on CP is advantageous.